Quantification and prediction of enteric methane emissions from Chinese lactating Holstein dairy cows fed diets with different dietary neutral detergent fiber/non-fibrous carbohydrate (NDF/NFC) ratios - Li-feng DONG; Peng JIA; Bin-chang LI; Bei WANG; Chun-lei YANG; Zhi-hao LIU; Qi-yu DIAO (Journal of Integrative Agriculture)
Methane (CH4) emissions from ruminant production are a significant source of anthropogenic greenhouse gas production, but few studies have examined the enteric CH4 emissions of lactating dairy cows under different feeding regimes in China. This study aimed to investigate the influence of different dietary neutral detergent fiber/non-fibrous carbohydrate (NDF/NFC) ratios on production performance, nutrient digestibility, and CH4 emissions for Holstein dairy cows at various stages of lactation. It evaluated the performance of CH4 prediction equations developed using local dietary and milk production variables compared to previously published prediction equations developed in other production regimes. For this purpose, 36 lactating cows were assigned to one of three treatments with differing dietary NDF/NFC ratios: low (NDF/NFC = 1.19), medium (NDF/NFC=1.54), and high (NDF/NFC=1.68). A modified acid-insoluble ash method was used to determine nutrient digestibility, while the sulfur hexafluoride technique was used to measure enteric CH4 emissions. The results showed that the dry matter (DM) intake of cows at the early, middle, and late stages of lactation decreased significantly (P<0.01) from 20.9 to 15.4 kg d−1, 15.3 to 11.6 kg d−1, and 16.4 to 15.0 kg d−1, respectively, as dietary NDF/NFC ratios increased. Across all three treatments, DM and gross energy (GE) digestibility values were the highest (P<0.05) for cows at the middle and late lactation stages. Daily CH4 emissions increased linearly (P<0.05), from 325.2 to 391.9 kg d−1, 261.0 to 399.8 kg d−1, and 241.8 to 390.6 kg d−1, respectively, as dietary NDF/NFC ratios increased during the early, middle, and late stages of lactation. CH4 emissions expressed per unit of metabolic body weight, DM intake, NDF intake, or fat-corrected milk yield increased with increasing dietary NDF/NFC ratios. In addition, CH4 emissions expressed per unit of GE intake increased significantly (P<0.05), from 4.87 to 8.12%, 5.16 to 9.25%, and 5.06 to 8.17% respectively, as dietary NDF/NFC ratios increased during the early, middle, and late lactation stages. The modelling results showed that the equation using DM intake as the single variable yielded a greater R2 than equations using other dietary or milk production variables. When data obtained from each lactation stage were combined, DM intake remained a better predictor of CH4 emissions (R2=0.786, P=0.026) than any other variables tested. Compared to the prediction equations developed herein, previously published equations had a greater root mean square prediction error, reflecting their inability to predict CH4 emissions for Chinese Holstein dairy cows accurately. The quantification of CH4 production by lactating dairy cows under Chinese production systems and the development of associated prediction equations will help establish regional or national CH4 inventories and improve mitigation approaches to dairy production.